Nate Silver. Issue 6 (December 2013) - Champkin, Julian; Oliver, Alison
<x xml:space="preserve">Abstract</x> Statistics will be the sexy profession of the next ten years. Hal Varian of Google said it, and it has become a cliché. Significance has been going for ten years, and in that time one man has made the prediction come true. Julian Champkin and Alison Oliver talked to Nate Silver.